1999
DOI: 10.1159/000028053
|View full text |Cite
|
Sign up to set email alerts
|

Synovial T Cell Receptor Heterogeneity in Early Arthritis

Abstract: Rheumatoid arthritis (RA) has been postulated to result from a synovial immune response to an unidentified antigen(s), which should be mirrored by the T cell response. Here we investigate the T cell receptor (TCR) repertoire in the synovial tissue of patients with arthritis of early to moderate duration. We developed a nested polymerase chain reaction (PCR) technique to examine the TCR repertoire of small biopsy specimens, and show that the method is highly sensitive. We apply this technique to synovial biopsi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2000
2000
2010
2010

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 48 publications
(57 reference statements)
0
2
0
Order By: Relevance
“…Although we have not formally demonstrated that CIIspecific T cells in the arthritic joints have a direct pathogenic function, it is clear that there is a selective attraction of these T cells that appear to have specificity for the autoantigen, and it seems likely that once there, they participate directly by either promoting the inflammation via soluble mediators or driving the production of autoantibody in situ. In RA, not only is there evidence of select T cell populations migrating to the inflamed joints (9,10,26,27,37), but the presence of organized lymphoid tissue resembling germinal centers has been also been demonstrated (38,39). It is interesting to consider that these in situ organizations of lymphocytes are responsible for the continual propagation of the inflammation in the affected joints.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although we have not formally demonstrated that CIIspecific T cells in the arthritic joints have a direct pathogenic function, it is clear that there is a selective attraction of these T cells that appear to have specificity for the autoantigen, and it seems likely that once there, they participate directly by either promoting the inflammation via soluble mediators or driving the production of autoantibody in situ. In RA, not only is there evidence of select T cell populations migrating to the inflamed joints (9,10,26,27,37), but the presence of organized lymphoid tissue resembling germinal centers has been also been demonstrated (38,39). It is interesting to consider that these in situ organizations of lymphocytes are responsible for the continual propagation of the inflammation in the affected joints.…”
Section: Discussionmentioning
confidence: 99%
“…It is interesting to consider that these in situ organizations of lymphocytes are responsible for the continual propagation of the inflammation in the affected joints. Unlike our model, studies examining the TCR expression by T cells infiltrating RA joints have resulted in a number of different observations regarding TCR-BV or AV usage, although many have indicated a limited or restricted repertoire present (9,10,26,27,37). Our model is based on a single known autoantigen that drives a restricted immune response primarily composed of T cells expressing BV8 and BV14.…”
Section: Discussionmentioning
confidence: 99%